EPIDEMIOLOGICAL PROFILE OF MALIGNANT SKIN NEOPLASM IN BRAZIL FROM 2018 TO 2023 - da Silva, Lucas Rocha Santana; Rocha, Diogo dos Santos; da Rocha, Fabiane Holanda Batista Porfirio; Trevilato, Pedro Victor Rocha; de Nardo, Ruan Carlos Ossuchi; Barros, Katia Talita dos Santos; Teixeira, Luciano de Castro Rezende Araujo; Sotero Filho, José Wilson Magalhães; de Brito, Pablo Vitor Almeida; Dovera, Pablo Diego Duarte; Ayres, Paulo Ricardo Antunes do Amaral; de Miranda, Ludycilla Nolasco (Seven Editora, 2024)
Objective: To define the epidemiological profile of malignant skin neoplasms in Brazil. Methods: This is a retrospective horizontal epidemiological profile that uses data from datasus with the years 2018 to 2023. Results: 44,735 hospitalizations were recorded in the period 2018-2023. As a result, more cases were observed in the age group of 60 years and over, in which 25,548 hospitalizations were reported. Discussion: The year 2020 had 6,387 hospitalizations, which represents a drop in the number of notifications compared to 2019 with 7,532 hospitalizations. When comparing the pandemic period with the post-pandemic period, an increase in the number of notifications was observed. There was possibly underreporting due to the overcrowding of hospitals during the pandemic period. Conclusion: In this sense, it is evident that the overcrowding of hospitals during the pandemic period was a determining factor for the decrease in reported cases as well as hospitalizations for skin cancer. The present study aims to inspire future public policies in the fight against malignant neoplasm of the skin. DOI: https://doi.org/10.56238/sevened2024.037-114